Zero tolerance: quality of life and the new police brutality in New York City - McArdle, Andrea; Erzen, Tanya (New York University Press, 2001)
Policing the quality of life. Turnstile jumpers and broken windows : policing disorder in New York City / Tanya Erzen -- Policing madness : people with mental illness and the NYPD / Heather Barr -- Giuliani time : urban policing and Brooklyn South / Sasha Torres -- The police. Can zero tolerance last? Voices from inside the precinct / Jennifer R. Wynn -- Girlz in blue : women policing violence in the NYPD / Amy S. Green -- No justice, no peace / Andrea Mcardle -- Activism. Mothers of Invention : the families of police-brutality victims and the movement they've built / Andrew Hsiao -- International human rights law and police reform / Paul Hoffman -- Police brutality in the New Chinatown. Committee Against Anti-Asian Violence. Organizing Asian communities -- An interview with Derrick Bell : reflections on race, crime, and legal activism / Andrea Mcardle -- Organizing at the intersections : a roundtable discussion of police brutality through the lens of race, class, and sexual identities / Dayo Folayan Gore, Tamara Jones, and Joo-Hyun Kang -- Bearing witness / Bradley Mccallum and Jacqueline Tarry